Exploring energy resilience: households’ perspectives on a changing power system - Hanna Björner Brauer; Maria Håkansson; Sara Willermark (Energy, Sustainability and Society)
Abstract Background In many countries, essential infrastructures, like power systems, are often taken for granted and thus invisible to ordinary people. However, because of energy transitions and climate impacts, the power system in countries such as Sweden is changing. For example, due to variable renewable power sources and increasing demand there is a potential need to deal with changing conditions, including disruptions at an end-use level, which makes the energy system come to the foreground. As argued in the paper, deeper knowledge about people’s understanding of a changing energy system is needed to support households in taking on new roles. The aim of this study was to explore energy resilience from a household perspective by investigating how households make sense of possible future power deficit scenarios. The concept of household energy resilience was used as a lens. Twelve interviews were conducted with people from seven households participating in a trial with remote-controlled heat pumps. The participating households all lived in detached houses in Sweden.  Results The findings illustrate how the households relate to energy resilience through diverse approaches. More specifically, they anticipate the need to become resilient while questioning the idea that they should have to become resilient, and negotiate resilience as a shared responsibility between the different stakeholders of the grid. These insights reveal conditions under which households anticipate taking more active roles in a changing energy system. However, the insights also show that other energy actors need to communicate clearly which responsibilities they are taking on to support households and the energy transition overall. Households cannot be expected to embrace household energy resilience without reciprocity and other actors’ taking on responsibility. Conclusions Our results show that there is potential for more active and engaged electricity end-users, beyond, for example, flexibility programs. However, households’ active participation, including becoming more energy resilient, is conditional on challenges of value, involvement, and reciprocity. The results will be of interest to professionals involved in electricity supply-related matters including suppliers, policymakers, and researchers.